Determinants of meeting the minimum acceptable diet among Filipino children aged 6-23 months - Guirindola, Mildred O.; Acuin, Cecilia Cristina S.; Silvestre, Catherine J.; Maniego, Ma. Lynell V. (2018)
Among children under the age of five, those aged 6-23 months are at a greater risk to suffer from malnutrition. Introduction of appropriate and safe foods to infants at the age of six months is recommended (WHO 2002) to meet evolving nutritional requirements for optimal growth, development, and good health (Ogbo et al. 2015). This secondary, cross sectional study using data from the 8th National Nutrition Survey in 2013 aimed to identify the determinants of meeting the minimum acceptable diet (MAD) among children 6-23 months and at age groups 6-11 mo, 12-17 mo, and 18-23 mo in the Philippines. Child, maternal, and household characteristics were examined in terms of their association with meeting the MAD using bivariate and multiple logistic regression analyses with a 5% level of significance (α=0.05). The final model showed that among children 6-23 mo, having a mother with more than three children (AOR=1.60) and being in the middle wealth quintile (AOR=1.88) had greater odds of meeting the MAD than those having a mother with at least three children and those in the poorest quintile, respectively. Children having more than five family members had lower odds (AOR=0.64) of meeting the MAD compared with less than five members. Among children 6-11 mo, those with more than five family members were more likely (AOR=5.32) to meet the MAD. Among 12-17 mo, children with non-working mothers (AOR=3.01) and those belonging to the rich wealth quintile (AOR=2.86) were more likely to meet the MAD while those with more than five family members were less likely (AOR=0.49) to meet the MAD. Children with low birth weight among 18-23 mo children had lower odds (AOR=0.47) of meeting the MAD. Working mothers, those from poorer quintiles, and those with more than five household members need to be specifically targeted for interventions that promote and encourage child feeding practices that meet the MAD.
Includes bibliographical references (pages 88-89)
Keywords: Nutrition; Complimentary feeding; Determinants; Filipino children; Minimum acceptable diet